Pengembangan Ternak Ruminansia Terintegrasi di Desa Koto Simandolak Kabupaten Kuantan Singingi: Pemanfaatan Jerami Padi untuk Pakan Ternak - Bakce, Djaimi; Mulyadi, Aras; Syahza, Almasdi; Adiwirman, Adiwirman; Rossi, Evy (Journal of Community Engagement Research for Sustainability, 2023)
The development of integrated ruminants includes activities to introduce, apply, and assist in the manufacture of amniotic and fermented straw animal feed techniques. The final goal is to make Koto Simandolak Village an independent village based on livestock. Persistently the community in Koto Simandolak Village has become better at developing ruminant livestock. In addition to meeting the needs of their own animal feed, ammoniated rice straw and fermented rice straw can be an alternative source of new income for the farmers who produce them.